Studi Kasus: Kesinambungan Perawatan pada Ny. “N” dengan Kehamilan Resiko Rendah - fitri, fitri yuniarti; Purwandari, Eka Sri; Basuki, Revi Baswantari (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Pregnancy and childbirth are normal, natural, and healthy processes. Pregnancy with Poedji Rochyati Score Card 2 is a low-risk pregnancy. Although low-risk, mothers must always be vigilant because every pregnancy is at risk of complications that can endanger the mother and fetus. The purpose of this case study is to provide midwifery care with Continuity of Care to Mrs. "N" from pregnancy, childbirth, postpartum, and neonate to the family planning period. The design of this study is a case study. The subject of this study was Mrs. "N" aged 27 years G2P1001 with a low-risk pregnancy. The research location was at TPMB Mrs. Erna, Tegowangi Village, Plemahan District, Kediri Regency from April 28, 2024 to July 5, 2024. The data collection method used observation, interviews, and documentation studies. The results of pregnancy care for Mrs. "N" if dizziness problems are found, they can be overcome with adequate rest, reduce stress with aromatherapy and relaxation massage, consume high-protein foods, and routinely consume iron tablets. The mother's labor process was normal vaginally and a normal delivery was carried out. During the postpartum period, problems were found, namely pain in the perineal stitches which could be overcome with relaxation, cold compresses on the stitches, not eating pants, consuming foods high in protein and fiber, and good personal hygiene, especially in the genital area. In neonates, no problems were found, and normal newborn care was carried out. During the birth control period, the mother chose to use an implant birth control according to the screening that had been carried out. Continuity of Care Midwifery care for Mrs. "N" was effectively given during pregnancy until birth control, as evidenced by the problems being resolved so that pregnancy until birth control went well and according to no complications.